Role of the Hydrophilic Channels of Simian Virus 40 T-Antigen Helicase in DNA Replication - Wang, Weiping (American Society for Microbiology, 2007)
The simian virus 40 (SV40) hexameric helicase consists of a central channel and six hydrophilic channels located between adjacent large tier domains within each hexamer. To study the function of the hydrophilic channels in SV40 DNA replication, a series of single-point substitutions were introduced at sites not directly involved in protein-protein contacts. The mutants were characterized biochemically in various ways. All mutants oligomerized normally in the absence of DNA. Interestingly, 8 of the 10 mutants failed to unwind an origin-containing DNA fragment and nine of them were totally unable to support SV40 DNA replication in vitro. The mutants fell into four classes based on their biochemical properties. Class A mutants bound DNA normally and had normal ATPase and helicase activities but failed to unwind origin DNA and support SV40 DNA replication. Class B mutants were compromised in single-stranded DNA and origin DNA binding at low protein concentrations. They were defective in helicase activity and unwinding of the origin and in supporting DNA replication. Class C and D mutants possessed higher-than-normal single-stranded DNA binding activity at low protein concentrations. The class C mutants failed to separate origin DNA and support DNA replication. The class D mutants unwound origin DNA normally but were compromised in their ability to support DNA replication. Taken together, these results suggest that the hydrophilic channels have an active role in the unwinding of SV40 DNA from the origin and the placement of the resulting single strands within the helicase.